2020
DOI: 10.1007/s43678-020-00010-w
|View full text |Cite
|
Sign up to set email alerts
|

Does utilization of an intubation safety checklist reduce omissions during simulated resuscitation scenarios: a multi-center randomized controlled trial

Abstract: Objectives Checklists have been used to decrease adverse events associated with medical procedures. Simulation provides a safe setting in which to evaluate a new checklist. The objective of this study was to determine if the use of a novel peri-intubation checklist would decrease practitioners’ rates of omission of tasks during simulated airway management scenarios. Methods Fifty-four emergency medicine (EM) practitioners from two academic centers were randomized to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
(5 reference statements)
0
13
0
1
Order By: Relevance
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 . Two of the trials were assessed to be at overall low risk of bias [ 27 , 33 , 34 ], nine to have some concerns [ 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 32 , 35 ] and two were at high risk of bias [ 20 , 21 ]. In the 13 instances where clarification of trial methodology or missing data was needed, seven authors responded with the required information [ 22 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Применение чек-листов при подготовке и выполнении интубации показало свою эффективность в отношении снижения частоты осложнений, развития гипоксемии и ошибок у разных категорий пациентов, в ряде случаев их применение незначимо увеличивает время подготовки к интубации [235][236][237][238][239][240]. Разработка чек-листов рекомендована рядом экспертов и профессиональных организаций как средство обеспечения безопасности пациентов во время ИТ [241][242].…”
Section: использование когнитивной помощи при обеспечении проходимост...unclassified